Pengembangan LKPD Pada Mata Pelajaran IPA Berbasis Project Based Learning Siswa Kelas V SDN 47 Lubuklinggau - Tri Novianto, Agustinus Eko; Mulyono, Dodik; Lokaria, Eka (LP4MK STKIP PGRI Lubuklinggau, 2024)
The objective of this research is to develop worksheets on science learning for fifth grade students of SD Negeri 47 Lubuklinggau and to produce valid, practical, and effective worksheets for students. This type of research is Research and Development using the ADDIE model. The subjects in this study were fifth grade students of SD N 47 Lubuklinggau, totaling 27 students. The data collection techniques used are interviews, questionnaires, and tests. Based on the results of the validity test of the three validators, namely linguists, materials, and media, the average result was 0.86 with the category